Perbandingan Analisis Cluster Kabupaten/Kota Di Provinsi Sulawesi Selatan Berdasarkan Luas Panen Dan Produksi Padi Menggunakan Average Linkage Method Dan Ward’s Method - Nurul Jusmahilda Ismail; Try Azisah Nurman; Adiatma (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to further examine the two best methods, namely the Average Linkage Method and Ward's Method obtained from previous researchers by grouping 24 Regencies/Cities in South Sulawesi Province based on the variables of harvested area and rice production in 2023. In this study, Euclidean and Squared Euclidean distance measures were used. Furthermore, the minimum standard deviation value within the cluster (Sw), the maximum standard deviation between clusters (Sb), and the minimum ratio of Sw to Sb were observed to determine the most effective method. And also seen from the best Dunn Index value in determining the optimum number of clusters for each method. Based on the formation of the dendogram, the number of clusters tested was 2 to 6 clusters. The results of the study explain that of the two methods used, the method with the best performance is the Average Linkage method with the formation of an optimum cluster of 3 clusters, where cluster I has a low level of rice productivity. Cluster II has a high level of rice productivity. Cluster III has a fairly high (medium) level of rice productivity. And in the Ward’s method, the optimum number of clusters formed is two clusters, with Cluster I having a low level of rice productivity and Cluster II having a high level of rice productivity.